Brief Report: Rate of Nicotine Metabolism and Tobacco Use Among Persons With HIV. (1st February 2019) - Schnoll, Robert A.; Thompson, Morgan; Serrano, Katrina; Leone, Frank; Metzger, David; Frank, Ian; Gross, Robert; Mounzer, Karam; Tyndale, Rachel F.; Weisbrot, Jessica; Meline, Miles; Collman, Ronald G.; et al.
Abstract : Background: The nicotine metabolite ratio (NMR) is a biomarker that represents individual variation in the speed that nicotine is metabolized. The rate of nicotine metabolism alters smoking behavior (eg, amount) and has been validated for personalizing tobacco dependence medication selection to increase treatment efficacy and reduce treatment side effects in the general population of smokers. Although smoking rates are extremely high among those with HIV, the NMR has not been evaluated in this underserved population. Methods: We used baseline data from a smoking cessation clinical trial for smokers with HIV (N = 131) to examine associations between NMR and demographic, smoking, disease-related, and psychological characteristics. Pearson r and analysis of variance were used to identify univariate correlates of NMR, which were then entered into a multiple linear regression model. Results: In univariate analyses, a higher NMR (faster nicotine metabolism) was associated with being white, and more cigarettes per day, nicotine dependence, exhaled carbon monoxide, and symptoms of depression and anxiety, and using efavirenz. In a multiple regression model, a higher NMR was associated with more cigarettes per day, higher anxiety symptoms, and efavirenz use. Conclusions: As in other populations, faster nicotine metabolism was associated with the use of more cigarettes and higher anxiety symptoms. Notably, efavirenz use was associated with faster metabolism, which might make it harder to quit smoking for people with HIV treated with that medication. These findings could help guide further study and the clinical use of the NMR to personalize nicotine dependence treatment in this underserved population.